Emphasizing the Importance of Hard Coal in Electricity Generation in Poland - Plewa, Franciszek; Strozik, Grzegorz (Recent Developments in Engineering Research Vol. 12, 2021)
Polish energy sector is facing a number of challenges, in particular as regards the reconstruction of production potential, diversification of energy sources, environmental issues, adequate fuels supplies and other. Mandatory implementation of Europe 2020 strategy in terms of “3x20” targets (20% reduction of greenhouse gases, 20% of energy from renewable sources, and 20% increase of efficiency in energy production) requires fast decision, which have to be coordinated with energetic safety issues, increasing demands for electric energy and other factors. Due to the fact that in Poland almost 80% of power is installed in coal fired power plants and energy from hard coals is relatively less expensive than the from other sources, especially renewable. The most of renewable energy sources related plants are unable to generate power in amount, which can be competitive with coal fires power stations and are highly expensive, what leads o high prices of electric energy. Alternatively, new generation of coal fired coal power plants is able to significantly increase efficiency, reduce carbon dioxide emission, and generate less expensive electric power in amounts adequate to the demands of a country. Production costs of electric energy will be influenced by buying of emission allowances and implementation of carbon dioxide capture and storage systems, however increased electric energy prices might be, at least in a part, compensated by achievement lower level of hard coal prices resulted from launching of new coal mines.